Combined use of real-time PCR and nested sequence-based typing in survey of human Legionella infection. Issue 9 (21st January 2016) - QIN, T.; ZHOU, H.; REN, H.; SHI, W.; JIN, H.; JIANG, X.; XU, Y.; ZHOU, M.; LI, J.; WANG, J.; SHAO, Z.; XU, X.
SUMMARY: Legionnaires' disease (LD) is a globally distributed systemic infectious disease. The burden of LD in many regions is still unclear, especially in Asian countries including China. A survey of Legionella infection using real-time PCR and nested sequence-based typing (SBT) was performed in two hospitals in Shanghai, China. A total of 265 bronchoalveolar lavage fluid (BALF) specimens were collected from hospital A between January 2012 and December 2013, and 359 sputum specimens were collected from hospital B throughout 2012. A total of 71 specimens were positive for Legionella according to real-time PCR focusing on the 5S rRNA gene. Seventy of these specimens were identified as Legionella pneumophila as a result of real-time PCR amplification of the dot A gene. Results of nested SBT revealed high genetic polymorphism in these L. pneumophila and ST1 was the predominant sequence type. These data revealed that the burden of LD in China is much greater than that recognized previously, and real-time PCR may be a suitable monitoring technology for LD in large sample surveys in regions lacking the economic and technical resources to perform other methods, such as urinary antigen tests and culture methods.